New perspectives on the evolutionary history of xiphosuran development through comparison with other fossil euchelicerates - Lustri, Lorenzo; Antcliffe, Jonathan B.; Saleh, Farid; Haug, Carolin; Laibl, Lukáš; Garwood, Russell J.; Haug, Joachim T.; Daley, Allison C. (Frontiers in Ecology and Evolution, 2023)
Euchelicerata is a diverse group encompassing Xiphosura, Chasmataspidida, Eurypterida, and Arachnida. Xiphosura represents an extant group with a rich fossil record dating back to the Ordovician period. Xiphosurans are often referred to as "living fossils" due to their seemingly unchanged morphology over millions of years. Numerous studies have contributed to the understanding of xiphosuran development, revealing changes in the timing and rate of their growth. These changes have been mainly associated with the freshwater invasion of early xiphosuran forms. However, limited research has been conducted to compare the developmental patterns of xiphosurans with other euchelicerates inhabiting aquatic environments. This study compares the developmental patterns of xiphosurans with that of the fossil clades of eurypterids and chasmataspidids. By incorporating environmental and phylogenetic information within ancestral state reconstruction analyses, and then testing different evolutionary scenarios, the influence of the environment on the evolution of developmental patterns of euchelicerates is examined. The results confirm that the developmental changes in Xiphosura throughout their evolutionary history are correlated with the exploitation of different environments. However, the inclusion of eurypterids and chasmataspidids indicates that the entirety of changes seen for Xiphosura represent only a small portion of the total variability recovered for euchelicerates, emphasizing the importance of considering phylogenetic relationships and outgroup comparisons to understand the evolutionary dynamics of Xiphosura.